ICT innovation: Cooperation for development [technology hubs, Zambia] - Lindunda, Lukonga (Technical Centre for Agricultural and Rural Cooperation, 2012)
The spirit of sharing is at the heart of the many new technology hubs that have opened in ACP countries in recent years. In Zambia, BongoHive encourages industry professionals to work with enthusiastic beginners to develop applications for the local mobile market